Faktor-Faktor yang Mempengaruhi Mahasiswa/i Memilih Program Studi Pariwisata Jurusan Pariwisata di Politeknik Negeri Samarinda - Sabalius Uhai; Rini Koen Iswandari; Musdalifah; Rina Oktavianti (Samarinda State Polytechnic, 2019)
His study aims to determine whether individual personality factors, job prospect factors, college image factors, and family support factors simultaneously influence the decision to choose a tourism study program at the Department of Tourism in Samarinda State Polytechnic? Do individual personality factors, job prospect factors, college image factors, and family support factors partially influence the decision to choose a tourism study program at the Department of Tourism in Samarinda State Polytechnic? This study uses multiple regression analysis and is used to analyze the results of the study. H1 accepted Then the individual personality factor variable has a dominant influence on the decision to choose a tourism study program. I can see that the count> table is (6,844)> (1,664) and a significant value of 0,000> 0,005. With the regression coefficient value is positive that is equal to 0, 414. I accepted then h1 the prospect of employment affects the decision to choose a tourism study program, I can see that the count> table is (2.581)> (1,664) and a significant value of 0.01 < 0.05. The regression coefficient value is positive at 0.277. H1 is accepted, then the image of the college influences the decision to choose tourism study programs. I can see that the value of dignity> table (1.432) <(1.664) With the positive coefficient of regression is 0.097 H1 is accepted then family support influences the decision to choose a study program tourism, it can be seen that the value of count> table is (2.007)> (1,664) and a significant value of 0.04 <0.05. Based on the ANOVA test, a Fcount of 45,947 can be obtained with a significant level of 0,000. Therefore, the probability is much smaller than 0.05 (0.000 <0.05) and Fcount> Table (45.947> 2.32), so it can be stated that the independent variables include individual personality factors (X1), employment prospect factors ( X2), college image factor (X3), and family support factor (X4) simultaneously or jointly influence the decision variable in choosing a tourism study program.